EXPLORING THE ROLE OF MICROCREDIT IN ENHANCING INCOME DIVERSIFICATION AMONG SMALLHOLDER FARMERS IN SOUTHEAST NIGERIA - Ogbonna, S. I.; Adole, P. O.; Muhammad, M. U. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study explored the role of microcredit in enhancing income diversification among Smallholder Farmers in Southeast Nigeria. A multistage sampling technique was used in selecting 360 respondents from the study area. Data were collected using structured questionnaire and analyzed using descriptive statistics, Student’s t-test, and probit regression analysis. The results showed that microcredit beneficiaries recorded a significantly higher mean income diversification index of 6.83 compared with 4.71 for non-beneficiaries, with the difference being statistically significant at the 1% level. The probit regression results further reveal that microcredit use exerted a positive and statistically significant effect on the likelihood of income diversification among farmers. Other important determinants of income diversification included age, level of education, household size, farm size, farming experience, distance to farm, labour cost, and cooperative membership. Age of respondents was negative and significantly related to income diversification at the 5% level. Level of education was positive and significant at the 1% level. Household size was positive and significant at the 5% level. Farming experience was positive and significant at the 1% level. Farming experience was positive and significantly related to income diversification at the 1% level. Distance to farm was positive and significant at the 1% level. This suggests that farmers who travel longer distances to their farms were more likely to diversify their income sources. Labour cost was negative and significant at the 10% level. This indicates that higher labour costs reduced the likelihood of income diversification among farming households. Cooperative membership was positive and significant at the 1% level. This shows that farmers who were part of cooperatives were more likely to diversify their income sources. Cooperative membership provides access to information, credit opportunities, and collective learning which encourages farmers to invest in additional livelihood activities. The findings indicate that access to microcredit reduces financial constraints and enhances farmers’ capacity to engage in multiple income-generating activities, thereby improving livelihood resilience. The study concludes that microcredit plays a critical role in promoting diversified livelihood strategies among rural farming households. It therefore recommended the need to strengthen rural microfinance delivery systems and integrating credit provision with complementary support services to enhance sustainable income diversification.